KINETICS OF HEXAFLUORIDE URANIUM - Kunakov, S.K. (Recent Contributions to Physics, 2018)
In the paper the kinetic model of the plasma  formed in an active zone of a nuclear reactor is submitted, and numerical calculation of ionic structure of plasma is lead.